Mewujudkan Generasi Emas dan Berkarakter Disiplin melalui Program Tahfidz Qur’an di SD IT Istiqomah - Mubarok, Husni; Ilya, Zunainatin; Nisa', Riska Kholiliya; Nisa’, Nurul Khoirun; Anintiya, Elisa Okta; Ahmad, Hendika Mukhoyyar (Lembaga Yasin AlSys, 2022)
The purpose of this study was to determine the learning contained in SD IT Istiqomah accompanied by a memorizing program of the Koran to create a golden and character generation. The method in writing is a qualitative descriptive method, then the search for the most relevant and main data related to the study of learning contained in SD IT Istiqomah is carried out through the memorization program of the Koran to create a golden and character generation. The purpose of this study was to determine the learning contained in SD IT Istiqomah accompanied by the Tahfidz qur'an program to create a golden and character generation. The method in writing is a qualitative descriptive method, then the search for the most relevant and main data related to the study of learning contained in SD IT Istiqomah is carried out through the memorization program of the Koran to create a golden and character generation. The results showed that the tahfidz qur'an program in SD IT Istiqomah was running well. The implementation of learning at SD IT Istiqomah is getting more quality with the addition of the tahfidz qur'an program, learning will be more interactive and with the tahfiz qur'an program also Islamic religious values will be embedded little by little in students at SD IT Istiqomah which will make them become generation of gold and character in accordance with Islamic values.